The Problem Solving Skills in Kindergarten Student Based on the Stages of Problem Solving - Anung Driyas Maraning Dyah; Farida Agus Setiawati (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2019)
The direct involvement of parents and teachers frequently appear in the problem solving which is faced by early childhood. Therefore, there are some problems that actually can be solved by children. This research aims to describe the level of childrens skill in solving the daily problem based on the problem solving thinking process. This research involve 25 children as participant in the range of age 4-6 years old in the Pertiwi Tumanggal Kindergarten. The collection of data was conducted by using interview technique. The data of childrens problem solving skill were quantitatively analysed. From the finding, it is obtained some results such as: (1) the most problem solving skill of children in Pertiwi Tumanggal Kindergarten is in medium category; (2) some items of statement which are still low are the reason to select the appropriate solution and the conviction in selecting the solutions